Complicated enterocele: timely resolution with bowel resection via a vaginal approach: case report - Abis, Paola; Madeddu, Clelia; Magro Malosso, Giovanni; Sole, Gabriele; Mereu, Alessia; Locci, Giorgia; Macciò, Antonio (Frontiers in Surgery, 2023)
Background Enterocele is an uncommon, serious condition that requires accurate and early diagnosis to prevent complications such as intestinal obstruction, incarceration, and strangulation, with consequent intestinal ischemia, necrosis, and evisceration. We report a rare case of a patient with a voluminous enterocele and initial signs of intestinal ischemia who underwent urgent vaginal surgery. Case description An 80-year-old woman presented with a voluminous mass protruding from the vagina, associated abdominopelvic pain, a 10-day history of bowel sub-occlusion, and numerous episodes of profuse vaginal bleeding. She was diagnosed with an enterocele with early signs of complications. Owing to her advanced clinical condition and comorbidities, we opted for an urgent vaginal procedure. Intestinal loops with initial signs of ischemia were resected via a transvaginal approach, leading to good clinical outcomes. She was discharged on postoperative day 5. Conclusions This rare case highlights a surgical emergency that was managed with transvaginal resection of the intestine. Early identification of the initial signs of complications allowed for this less invasive approach, resulting in reduced morbidity and length of hospital stay.